Investigation of ferroresonance phenomena in isolated 6 kV power network - Jasika, Ranko; Maksić, Katarina; Mrvić, Jovan (Proceedings, Electrical engineering institute "Nikola Tesla", 2023)
Ferroresonance is a complex nonlinear electrical phenomenon that can cause significant dielectric and thermal stresses in power equipment, leading to potential faults, equipment damage, power supply interruptions, etc. Three-phase networks with isolated neutral point and single-phase isolated inductive voltage transformers are susceptible to ferroresonance, caused by the interaction of the transformer’s nonlinear inductances and zero sequence capacitance of power network. The paper analyzes the possibility of ferroresonance occurrence in a real 6 kV power network, with an isolated neutral point, using the electromagnetic transients program ATP/EMTP. A detailed network model is developed, taking into account the nonlinearity of voltage and power transformers, which is utilized to analyze various configurations, switching operations, and faults in the network that could trigger ferroresonance. It is shown that, under certain circumstances, ferroresonance can occur, with faults clearing being the most common initiators of ferroresonance. The efficiency of different measures to suppress ferroresonance is also analyzed. The impact of the resistance values of voltage transformer’s open delta winding dumping resistor on the suppression of ferroresonance occurrence, is considered.